Fresh and hardened properties of polymer incorporated self compacting concrete mixes for neutron radiation shielding. (30th December 2017) - Malkapur, Santhosh M.; Divakar, L.; Narasimhan, Mattur C.; Karkera, Narayana B.; Goverdhan, P.; Sathian, V.; Prasad, N.K.
Highlights: Hydrogen content is critical in shielding neutron radiation. Pulverised high density polyethylene (HDPE) used as source of hydrogen to develop new concrete mixes. The HDPE material was incorporated as a partial replacement to river sand. These mixes are calledP olymer-I ncorporatedS elf-C ompactingC oncrete (PISCC) mixes . The PISCC mixes have satisfactory fresh and hardened properties and enhanced neutron radiation shielding properties. Abstract: Several works in the past have reported that the hydrogen content in the hydrated concrete plays an important role in shielding the neutron radiation; higher the hydrogen content, better is the neutron radiation shielding. In this study, pulverised high density polyethylene (HDPE) material is used as an additional source of hydrogen within concrete to develop a novel class ofP olymer-I ncorporatedS elf-C ompactingC oncrete (PISCC) mixes for enhanced neutron radiation shielding. The HDPE material was incorporated as a partial replacement to river sand. It is found that the PISCC mixes have satisfactory fresh and hardened properties and enhanced neutron radiation shielding properties.